2021
DOI: 10.1007/978-3-030-84242-0_15
|View full text |Cite
|
Sign up to set email alerts
|

On the Round Complexity of Secure Quantum Computation

Abstract: Can a sender non-interactively transmit one of two strings to a receiver without knowing which string was received? Does there exist minimally-interactive secure multiparty computation that only makes (black-box) use of symmetric-key primitives? We provide affirmative answers to these questions in a model where parties have access to shared EPR pairs, thus demonstrating the cryptographic power of this resource.• First, we construct a one-shot (i.e., single message) string oblivious transfer (OT) protocol with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…We note that while prior work [BCKM21a] has implicitly constructed a two-message zeroknowledge state synthesis protocol in the CRS model, our work is the first to obtain this primitive with one message in the shared EPR pair model. Corollary 4.25.…”
Section: Zero-knowledge State Synthesis State Synthesis [Aar16 Ry22 Innmentioning
confidence: 99%
See 3 more Smart Citations
“…We note that while prior work [BCKM21a] has implicitly constructed a two-message zeroknowledge state synthesis protocol in the CRS model, our work is the first to obtain this primitive with one message in the shared EPR pair model. Corollary 4.25.…”
Section: Zero-knowledge State Synthesis State Synthesis [Aar16 Ry22 Innmentioning
confidence: 99%
“…We now use a result from [BCKM21a] showing that any unidirectional quantum functionality can be securely computed in one message given access to a secure one-message protocol for arbitrary unidirectional classical functionalities. Since this theorem is not explicitly stated in [BCKM21a], we add some explanation for how it follows from their work.…”
Section: Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since MPQC is closely related to QPFE, we give a brief review of MPQC here. A more comprehensive review of the field of MPQC can be found in [9]. In the first work of MPQC [8], Crepeau et al present an information-theoretically secure MPQC protocol when the proportion of malicious parties is less than 1/6.…”
Section: Mpqcmentioning
confidence: 99%